2012
DOI: 10.1186/1472-6882-12-2
|View full text |Cite
|
Sign up to set email alerts
|

The use of complementary and alternative medicine among people living with diabetes in Sydney

Abstract: BackgroundComplementary and alternative medicine (CAM) is common in patients with chronic disease such as diabetes mellitus. The primary objective of the study was to determine the overall prevalence and type of CAM use in individuals with diabetes mellitus (DM) in Western Sydney and to compare the prevalence and factors associated with CAM use with the literature.MethodsA multicenter cross-sectional study was undertaken using a self-completed questionnaire distributed to patients with DM attending a public ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
70
0
11

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 15 publications
4
70
0
11
Order By: Relevance
“…Çalışmamızda bitkisel uygulamalara ek olarak dua'nın (%32.7) en sık tercih edilen TAT yöntemi arasında yer aldığı görülmüştür. Literatürde yapılan çalışmalarda, dua yönteminin hastaları psikolojik olarak rahatlatmasından dolayı sık tercih edildiği bildirilmektedir (22,27,28).…”
Section: Discussionunclassified
“…Çalışmamızda bitkisel uygulamalara ek olarak dua'nın (%32.7) en sık tercih edilen TAT yöntemi arasında yer aldığı görülmüştür. Literatürde yapılan çalışmalarda, dua yönteminin hastaları psikolojik olarak rahatlatmasından dolayı sık tercih edildiği bildirilmektedir (22,27,28).…”
Section: Discussionunclassified
“…The use of traditional medicine is prevalent among patients with chronic health problems (1,2), including diabetes (1)(2)(3)(4)(5)(6). A review of traditional medicine use among diabetes populations showed that the prevalence of traditional medicine usage ranged from 17% to 72.8% (7).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, several studies have examined the influence of sociodemographic and clinical characteristics of diabetes patients on traditional medicine use (4,8,14). Moreover, a review of traditional medicine use among diabetic populations has indicated that some sociodemographic and clinical factors are associated with greater use of traditional medicine (7).…”
Section: Introductionmentioning
confidence: 99%
“…4 The popularity of TM and CAM has increased in recent years, especially in developed countries. [5][6][7] Recent studies indicate that a substantial number of people use CAM therapies in their lifetime with the expectation of maintaining and promoting health and curing diseases. [8][9][10] Ayurveda is an ancient medicine that originated in the Indian subcontinent.…”
Section: Introductionmentioning
confidence: 99%